2020
DOI: 10.21203/rs.2.18357/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral Nystatin Prophylaxis to Prevent Systemic Fungal Infection in Very Low Birth Weight Preterm Infants : A Randomized Controlled Trial

Abstract: Background Systemic fungal infection (SFI) is one of leading causes of morbidity and mortality in very low birth weight (VLBW) preterm infants. Because early diagnosis of SFI is challenging due to nonspecific manifestations, prophylaxis becomes crucial. This study aimed to assess effectiveness of oral nystatin as an antifungal prophylaxis to prevent SFI in VLBW preterm infants. Methods A prospective, open-labelled, randomized controlled trial was performed in a neonatal intensive care unit (NICU) of an academi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 46 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Figure 1 shows the PRISMA flow chart for our screening steps. Overall, five RCTs met our criteria and were included in the final analysis [7,[15][16][17][18]. A total of 1750 participants were enrolled in these studies (n=884 participants were allocated to nystatin group and n=866 participants were allocated to the control group).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 1 shows the PRISMA flow chart for our screening steps. Overall, five RCTs met our criteria and were included in the final analysis [7,[15][16][17][18]. A total of 1750 participants were enrolled in these studies (n=884 participants were allocated to nystatin group and n=866 participants were allocated to the control group).…”
Section: Resultsmentioning
confidence: 99%
“…The summary and baseline characteristics of the included studies are shown in Table 1 and Table 2, respectively. Figure 2 shows the risk of bias summary of the included studies [7,[15][16][17][18]. Three RCTs showed overall "low risk" of bias [7,16,17], one RCT revealed overall "some concerns/unclear risk" of bias [18], and one RCT revealed overall "high risk" of bias [14].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations